(untitled) (Indian Journal of Animal Production and Management, 2024)
Effect of non-genetic factors viz., with or without calf stimulus at milking i.e., restricted suckling or non suckling, age and body weight of first calvers, parity and season of calving on lactation and reproductive performance of 194 Gir cows were investigated. Lactation days (LL), total lactation milk yield (TLMY),300-d milk yield (SLMY), peak yield/day (PY), days to attain peak yield (D-PY), uterine involution time post-partum (D-UI), post-partum oestrus interval (PPOI) and service period (SP) of farm born Gir females, calving / drying during April, 2009 to March, 2012 at CBF, Junagadh were analyzed. Over-all LL, TLMY, SLMY, PY, D-PY, D-UI, PPOI and SP of the Gir cows were 337.62±7.89 days,1838.25±64.94 lit ,1637.87±50.56 lit ,10.29±0.22 lit/day ,58.73±0.65 days, 33.04 ±0.51 days, 94.00±1.34 days and 179.51±3.08 days, respectively. Calf rearing method, age and body weight of first calvers and season of calving did not influence significantly the performance traits. However, reproductive performance was significantly (P<0.05) and adversely affected in the cows under restricted suckled group. Non-suckling in Gir cows (weaning at birth and artificial rearing) does not adversely affect the performance and almost equal amount (1800 lit/ lactation and 1600 lit in 300 days) of milk produced in restricted suckling could be obtained. SLMY in multiparous cows was 290 lit more than that in primiparous cows. AFC of 1400 to 1700 days with more than 295-330 kg body weight produced 1550 to 1700 liter in their first lactation.